Peran Manajemen Kepemimpinan Dalam Meningkatkan Kinerja Guru Madrasah Aliyah di Bengkulu - Sarah Wulandari; Errick Avra; Reri Aprizal; Diana Riyanti; Yesi Agustina; Novya Safitri; Pardi Pardi; Elvina Rosa (Al-Khair Journal: Management Education, 2023)
Abstract: Teacher performance is still relatively low, characterized by the low ability of teachers to meet educational standards, such as pedagogic competence, personality competence, social competence, and professional competence both partially and simultaneously. The purpose of this study is to map and analyze the role of leadership management in improving teacher performance. Using descriptive qualitative methods with literature review education. Sources of information are obtained from scientific books, scientific articles both nationally and internationally. The results showed that the role of leadership management became very decisive and very important in improving teacher performance. Leadership has played a role in managing educational institutions, seen changes made by leadership, innovating, playing a role in growing school culture, acting as a work partner, has established cooperation between school residents and has organizational goals. Especially playing a role in improving teacher performance such as always providing guidance, direction to teachers, so that teachers have the ability to carry out their main duties, functions and responsibilities. Such as, compiling lesson plans, implementing learning, evaluating learning outcomes, carrying out follow-up learning achievement results. Thus, it can be suggested to improve teacher performance, hence increase the role of leadership management in madrasas.Keywords: Roles, Leadership Management, Teacher Performance Abstrak: Kinerja guru masih tergolong rendah, ditandai dengan rendahnya kemampuan guru dalam memenuhi standar pendidikan, seperti kompetensi pedagogic, kompetensi kepribadian, kompetensi sosial, dan kompetensi professional baik secara parsial maupun simultan. Tujuan penelitian ini untuk memetakan dan menganalisis peran manajemen kepemimpinan dalam meningkatkan kinerja guru. Menggunakan metode kualitatif deskriptif dengan pendidikan kajian pustaka. Sumber informasi didapat dari buku-buku ilmiah, artikel-artikel ilmiah baik nasional maupun internasional. Hasil penelitian menunjukkan bahwa peran manajemen kepemimpinan menjadi sangat menentukan dan sangat urgen dalam meningkatkan kinerja guru. Kepemimpinan telah berperan mengelola lembaga pendidikan, terlihat perubahan yang dilakukan oleh kepemimpinan, melakukan inovasi, berperan dalam menumbuhkan budaya sekolah, berperan sebagai partner kerja, telah menjalin kerjasama antar warga sekolah dan memiliki tujuan organisasi. Khususnya berperan dalam meningkatkan kinerja guru seperti senantiasa memberikan bimbingan, arahan kepada guru-guru, sehingga para guru telah memiliki kemampuan dalam menjalankan tugas pokok, fungsi dan tanggungjawabnya. Seperti, menyusun rencana pembelajaran, melaksanakan pembelajaran, melakukan evaluasi hasil pembelajaran, melaksana tindak lanjut hasil prestasi pembelajaran. Dengan demikian, dapat disarankan untuk meningkatkan kinerja guru, maka tingkatkan peran manajemen kepemimpinan di madrasah.Kata kunci: Peran, Manajemen Kepemimpinan, Kinerja Guru